Defects of properties in mathematics quantitative characterizations - Ban, Adrian I.; Gal, Sorin G., 1953-; ebrary, Inc. (Singapore ; River Edge, NJ : World Scientific, 2002)
"This book introduces a method of reasearch which can be used in various fields of mathematics. It examines, in a systematic way, the quantitative characterizations of the "deviation from a (given) property", called the "defect of a property", in: set theory; topology; measure theory; real, complex and functional analysis; algebra; geometry; number theory; fuzzy mathematics"--P. [2] of cover.
Includes bibliographical references (p. 337-348) and index.
Electronic reproduction.
Keywords: Deviation (Mathematics); Fuzzy mathematics; Mathematics; Electronic books